Dengue virus and Zika virus alter endoplasmic reticulum-mitochondria contact sites to regulate respiration and apoptosis - Wesley Freppel; Viviana Andrea Barragan Torres; Olus Uyar; Anaïs Anton; Zaynab Nouhi; Mathilde Broquière; Clément Mazeaud; Aïssatou Aïcha Sow; Alexanne Léveillé; Claudia Gilbert; Nicolas Tremblay; Jonathan Eintrez Owen; et al. (iScience)
Summary: During infection, dengue virus (DENV) and Zika virus (ZIKV), two (ortho)flaviviruses of public health concern worldwide, induce alterations of mitochondria morphology to favor viral replication, suggesting a viral co-opting of mitochondria functions. Here, we performed an extensive transmission electron microscopy-based quantitative analysis to demonstrate that both DENV and ZIKV alter endoplasmic reticulum-mitochondria contact sites (ERMC). This correlated at the molecular level with an impairment of ERMC tethering protein complexes located at the surface of both organelles. Furthermore, virus infection modulated the mitochondrial oxygen consumption rate. Consistently, metabolomic and mitoproteomic analyses revealed a decrease in the abundance of several metabolites of the Krebs cycle and changes in the stoichiometry of the electron transport chain. Most importantly, ERMC destabilization by protein knockdown increased virus replication while dampening ZIKV-induced apoptosis. Overall, our results support the notion that flaviviruses hijack ERMCs to generate a cytoplasmic environment beneficial for sustained and efficient replication.